Natural enemies and biodiversity: The double-edged sword of trophic interactions - Alexandre Mestre; Robert D. Holt (Mètode Science Studies Journal: Annual Review)
Natural enemies, that is, species that inflict harm on others while feeding on them, are fundamental drivers of biodiversity dynamics and represent a substantial portion of biodiversity as well. Along the life history of the Earth, natural enemies have been involved in probably some of the most productive mechanisms of biodiversity genesis; that is, adaptive radiation mediated by enemy-victim coevolutionary processes. At ecological timescales, natural enemies are a fundamental piece of food webs and can contribute to biodiversity preservation by promoting stability and coexistence at lower trophic levels through top-down regulation mechanisms. However, natural enemies often produce dramatic losses of biodiversity, especially when humans are involved.